The Need to Reconceptualize the Permanent Establishment Threshold - Pinto, Dale (International Bureau of Fiscal Documentation (IBFD), 2006)
This article contends that the way source is defined under the permanent establishment threshold for purposes of the OECD Model Tax Convention is no longer valid and should be reconceptualized in light of the changes brought about by globalization and the related developments in electronic commerce. The article first considers whether source-based taxation remains theoretically valid in today's globalized business world. The article then addresses the central issue of the need to reconceptualize the permanent establishment threshold as currently defined. The definition of permanent establishment in the OECD Model requires either a physical presence or a representative presence for source-based taxation. Globalization, epitomized by the advent of electronic commerce, allows substantial business activities to take place in a source state without either physical or human intermediaries, making it more difficult to find a permanent establishment based on its traditional formulation in the OECD Model. Rather than relying on a physical or representative presence for a permanent establishment, this article suggests a different threshold and undertakes an analysis of three possible approaches: the base-erosion approach, the virtual permanent establishment approach, and the refundable withholding approach. The article examines the advantages and disadvantages of each approach.